2006
DOI: 10.1037/0021-843x.115.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and the development of nicotine, alcohol, and illicit drug disorders: Prospective links from adolescence to young adulthood.

Abstract: The personality traits constraint (CN) and negative emotionality (NE) have been more (CN) or less (NE) consistently associated with alcoholism. The authors examined the association of personality at age 17 with timing of onset and with prospective prediction of nicotine, alcohol, and illicit drug disorders 3 years later in a twin sample (569 females; 432 males). Earlier onset of alcohol and drug disorders (by age 17) was related to significantly lower CN compared with later onsets (by age 20); high NE was rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
2
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(149 citation statements)
references
References 67 publications
7
136
2
4
Order By: Relevance
“…The BD liability is expressed as different phenotypes over the course of development with the same early temperament traits predicting various subsequent EXT disorders. Behavioral disinhibition traits, such as lack of inhibitory control, novelty seeking, and low harm avoidance, when expressed during early childhood predict subsequent substance use and misuse during adolescence (Caspi, Henry, McGee, Moffitt, & Silva, 1995;Caspi et al, 1996;Masse & Tremblay, 1997;Wong et al, 2006), and the same traits assessed during late childhood, adolescence, and young adulthood predict tobacco, alcohol, and illicit drug symptoms and disorders in later in adulthood (Chassin, Fora, & King, 2004;Cloninger, Sigvardsson, & Bohman, 1988;Elkins et al, 2006;Grekin, Sher, & Wood, 2006;Krueger, 1999a;Sher, Bartholow, & Wood, 2000). These traits also manifest as disruptive behavior disorders (e.g., Oppositional Defiant Disorder, CD) during childhood (Young, et al, 2009), which are predictive of later SUDs (Kim-Cohen et al, 2003;Weinberg, Rahdert, Colliver, & Glantz, 1998), and as high-risk behaviors during early adolescence, such as antisocial behavior, experimentation with alcohol, precocious sexual activity, and academic difficulty, which in turn predict later SUDs and ASPD (Grant & Dawson, 1997;.…”
Section: Behavioral Disinhibition Liability For Externalizing Disordersmentioning
confidence: 99%
“…The BD liability is expressed as different phenotypes over the course of development with the same early temperament traits predicting various subsequent EXT disorders. Behavioral disinhibition traits, such as lack of inhibitory control, novelty seeking, and low harm avoidance, when expressed during early childhood predict subsequent substance use and misuse during adolescence (Caspi, Henry, McGee, Moffitt, & Silva, 1995;Caspi et al, 1996;Masse & Tremblay, 1997;Wong et al, 2006), and the same traits assessed during late childhood, adolescence, and young adulthood predict tobacco, alcohol, and illicit drug symptoms and disorders in later in adulthood (Chassin, Fora, & King, 2004;Cloninger, Sigvardsson, & Bohman, 1988;Elkins et al, 2006;Grekin, Sher, & Wood, 2006;Krueger, 1999a;Sher, Bartholow, & Wood, 2000). These traits also manifest as disruptive behavior disorders (e.g., Oppositional Defiant Disorder, CD) during childhood (Young, et al, 2009), which are predictive of later SUDs (Kim-Cohen et al, 2003;Weinberg, Rahdert, Colliver, & Glantz, 1998), and as high-risk behaviors during early adolescence, such as antisocial behavior, experimentation with alcohol, precocious sexual activity, and academic difficulty, which in turn predict later SUDs and ASPD (Grant & Dawson, 1997;.…”
Section: Behavioral Disinhibition Liability For Externalizing Disordersmentioning
confidence: 99%
“…We only consider prospective studies of adolescents that restricted their analyses to samples of smokers to ensure that predictors are unique to dependence and do not characterize smoking more generally. Thus, we do not review studies where those dependent were compared to all those not dependent, including subjects who never smoked (Elkins et al, 2006;Fergusson et al, 1996;Patton et al, 2005).…”
Section: Correlates and Predictors Of Nicotine Dependencementioning
confidence: 99%
“…There has been limited sample attrition over the successive waves of assessments, with from 80-93% of surviving twins participating at each follow-up assessment. For example, Elkins et al (2006) report that in the older cohort 83% of males and 93% of females from the older cohort completed their first follow-up assessment, while reported that 92% of males and 94% of females from the younger cohort completed their first follow-up assessment. Importantly, in all cases non-participants differ minimally, although in some cases significantly, from participants in terms of their status on the intake assessments.…”
Section: Samplementioning
confidence: 99%